Genotype-specific responses of maize plants to Funneliformis mosseae under drought stress: phenomic and transcriptomic insights - Virág, Eszter; Zombori, Zoltán; Hóvári, Miklós; Hegedűs, Géza; Sass, László; Ferenc, Györgyi; Dudits, Dénes; Posta, Katalin (Frontiers in Plant Science, 2026)
IntroductionDrought is a major abiotic constraint limiting maize productivity, yet the genotype-specific mechanisms through which arbuscular mycorrhizal fungi (AMF) enhance drought resilience remain poorly understood. This study aimed to elucidate how AMF modulate drought tolerance, root plasticity, and heterosis in maize genotypes with contrasting drought sensitivity.MethodsTwo maize inbred lines differing in drought tolerance (K1, tolerant; K2, sensitive) and their hybrid (KH) were grown under controlled pot conditions at either well-watered (60% soil moisture) or drought-stressed (30% soil moisture) levels, with or without inoculation with Funneliformis mosseae (BEG12). Integrated phenomic, biomass, and transcriptomic analyses were performed to characterize genotype-specific AMF responses.ResultsAMF induced distinct, genotype-dependent responses under drought stress. In K1 plants, AMF maintained drought tolerance by stabilizing photosynthetic performance, supported by sustained expression of PSI, PSII, LHCb, and Calvin-cycle genes, alongside the activation of CYP450 71A1 and CONSTANS-like 3, suggesting auxin-associated regulation of stress adaptation. In contrast, drought strongly suppressed photosynthetic gene expression in K2 plants, while AMF promoted pronounced root system expansion accompanied by the induction of indole-3-acetaldehyde oxidase, auxin-binding protein 1, CORONATINE-INSENSITIVE 1, and tasselseed-2, indicating hormone-driven root plasticity and modified reproductive signaling. In the hybrid KH, selective activation of RbcX and heterosis-associated genes supported biomass stability and consistent flowering, although AMF had limited effects on hybrid vigor.DiscussionThese findings reveal distinct molecular strategies underlying AMF-mediated drought resilience in maize, demonstrating that drought-sensitive genotypes primarily benefit through enhanced root plasticity, whereas drought-tolerant genotypes maintain photosynthetic stability. Overall, the results highlight the potential of targeted AMF–genotype combinations to improve water-use efficiency and promote sustainable maize production under drought stress.